Robotics and the Islamic worldview: a Tawhidic epistemology framework for ethical and human-centered technological innovation - Shafie, Amir Akramin; Che Cob, Saiful Akram (Faculty of Islamic Technology, UNISSA, 2026)
This paper explores the integration of robotics within the Islamic worldview, proposing a Tawhidic epistemology as a foundational framework for ethical and human-centered technological innovation. Modern robotics influences nearly every sector—from manufacturing and medicine to education and environmental stewardship—yet its rapid evolution generates profound moral and social challenges. Drawing upon the principles of Tawhid (Oneness of God), Khilafah (stewardship), and Maqasid al-Shariah (objectives of Islamic law), this paper examines how Islamic epistemology unifies scientific progress with divine purpose. Through philosophical analysis and illustrative examples, it argues that robotics, when guided by Tawhidic consciousness, becomes an act of stewardship (amanah) rather than domination. The paper concludes that Islamic ethics can provide a comprehensive moral compass for robotics governance—one grounded in justice (‘adl), compassion (rahmah), and sustainability (istiqamah).